2012
DOI: 10.1016/j.gca.2011.10.044
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the interaction of basaltic riverine particulate material and seawater

Abstract: The riverine transport of elements from land to ocean is an integral flux for many element cycles and an important climate regulating process over geological timescales. This flux consists of both dissolved and particulate material. The world's rivers are estimated to transport between 16.6 and 30 Gt yr À1 of particulate material, considerably higher than the dissolved flux of $1 Gt yr À1 . Therefore, the dissolution of particulate material upon arrival in estuaries and coastal waters may be a significant flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 67 publications
9
82
0
Order By: Relevance
“…4b), the volcanics contribute $12% to the bulk detrital sediment Nd budget. Therefore, if contamination of the leachates only occurs from the volcanic component, $8% dissolution of this phase is required, in good agreement with recent studies on the dissolution of volcanic materials (Jones et al, 2012). Based on the same approach, the small samples of experiment (i) on WIND 24B also require $8% dissolution of this volcanic phase, while comparable calculations for small samples from WIND 28B and WIND 32B are also consistent with $5-10% dissolution.…”
Section: Preferential Dissolution Of a Volcanic Componentsupporting
confidence: 84%
See 1 more Smart Citation
“…4b), the volcanics contribute $12% to the bulk detrital sediment Nd budget. Therefore, if contamination of the leachates only occurs from the volcanic component, $8% dissolution of this phase is required, in good agreement with recent studies on the dissolution of volcanic materials (Jones et al, 2012). Based on the same approach, the small samples of experiment (i) on WIND 24B also require $8% dissolution of this volcanic phase, while comparable calculations for small samples from WIND 28B and WIND 32B are also consistent with $5-10% dissolution.…”
Section: Preferential Dissolution Of a Volcanic Componentsupporting
confidence: 84%
“…Few experimental studies have addressed these questions or investigated boundary exchange more generally. A boundary exchange process occurred in batch reactor experiments on various riverine sediments but not on the one estuarine sediment sample studied to date (Jones et al, 2012). Since estuarine sediments are likely to represent more closely the material that is transferred to the oceans, we do not yet have experimental evidence to support the observational evidence for boundary exchange in the deep ocean (Lacan and Jeandel, 2005).…”
Section: Introductionmentioning
confidence: 86%
“…Batch experiments or sequential leaching slightly illuminated the processes by confirming that a fraction of the lithogenic material can be dissolved, releasing some of the elements it contains and contributing to balance their isotopic composition [29][30][31][32]51]. These experiments also showed that secondary phases are rapidly formed, scavenging a large part of most of the released species.…”
Section: (D) What Do the Models Tell Us?mentioning
confidence: 88%
“…However, because seawater is close to saturated or supersaturated with respect to many mineral phases, much of the chemical input into seawater from atmospheric or riverine transported particulate material dissolution should be readily precipitated as secondary mineral, consistent with the 'Boundary Exchange' hypothesis. This could affect the net element input flux, but not so clearly its isotopic composition and the impact of this composition on the local seawater [29][30][31][32]. Precise flux estimates will depend on a comprehensive understanding of processes governing particle-solution exchanges, opening a large field for further researches.…”
Section: Introductionmentioning
confidence: 99%
“…When transferred to the oceans, the Ca 2+ adsorbed on sediment surfaces is partially exchanged for Na + , Mg 2+ and K + (Sayles and Mangelsdorf, 1977), which are more abundant in ocean waters. These exchange reactions represent an additional source of Ca to the oceans and a potential sink for Na, Mg and K. These estuarine exchange reactions cannot be directly compared to additional weathering fluxes from the chemical weathering of sediments in seawater that has recently been suggested (Jones et al, 2012) as the processes are different. Chemical weathering in the presence of seawater involves the formation of secondary minerals (Jones et al, 2012), which is not the case for exchange reactions.…”
mentioning
confidence: 99%